Times of Insight: Conscience, Corporations, and the Common Good - Goodpaster, Kenneth E. (Eminent Voices in Business Ethics,, 2022)
This open access book traces the research and teaching contributions of Kenneth Goodpaster over more than 45 years of his career. The book shows the content and the progression of these themes over the years identifying four insights in applied ethics: the moral insight, the institutional insight, the anthropological insight, and the Socratic insight. It highlights such concepts as conscience, corporate responsibility, corporations as agents and as recipients, stockholders, stakeholders, comprehensive moral thinking, and ethics education. In addition, Goodpaster explains phrases such as teleopathy, moral projection, human dignity, and the common good. Finally, the book examines with concern the implications of the foregoing for the polarizing and partisan trends in contemporary business behavior.